E-Archive : Digital Storage Media - Arnes Yuli Vandika; Ade Kurniawan; Ari Kurniawan Saputra (International Conference on Engineering and Technology Development (ICETD), 2014)
In the digital age that is increasingly sophisticated, that have an impact on all aspects of our daily lives, one of them is on the filing system on the experience the more effective and efficient, which previously used the closet as storage media, we can now utilize electronics as the storage media archives. Application of the method of filing electronically in an institution is required to support the activities of archiving that achieved effectiveness and efficiency in the management, as well as being able to secure the archives that have important information or value for its users. In the implementation of an electronic archive, type of media used all kinds such as E-mail, DVD 's, microfilm and other electronic media. To support the activities of the application required a good infrastructure and facilities for monitoring and maintenance so that the planned goals are achieved. It also needed a system that is appropriate for the application that is executed is supported by personnel competent in the field of archiving, as well as having the skills and capabilities that support the implementation of electronic filing.